The Use of Artificial Intelligence (AI) in Academic Writing and Publishing Papers - van Teijlingen, Edwin; Subedi, Madhusudan; Parker, Sara; Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2024)
Use of AI